Design, preparation, and selection of DNA-encoded dynamic libraries. Issue 12 (21st September 2015) - Li, Gang; Zheng, Wenlu; Chen, Zitian; Zhou, Yu; Liu, Yu; Yang, Junrui; Huang, Yanyi; Li, Xiaoyu
Abstract : DNA-encoded dynamic libraries (DEDLs) are realized by dynamic DNA hybridization and a novel equilibrium-locking mechanism. Abstract : We report a method for the preparation and selection of DNA-encoded dynamic libraries (DEDLs). The library is composed of two sets of DNA-linked small molecules that are under dynamic exchange through DNA hybridization. Addition of the protein target shifted the equilibrium, favouring the assembly of high affinity bivalent binders. Notably, we introduced a novel locking mechanism to stop the dynamic exchange and "freeze" the equilibrium, thereby enabling downstream hit isolation and decoding by PCR amplification and DNA sequencing. Our DEDL approach has circumvented the limitation of library size and realized the analysis and selection of large dynamic libraries. In addition, this method also eliminates the requirement for modified and immobilized target proteins.